Student study approach preferences and motivation in teacher training in Malaysia - Hamdan, Abdul Rahim (2004)
The purpose of the study was to explore how the students' study approach preferences and levels of motivation in teacher training differed between traditional [pre-service teacher] and non-traditional [in-service teacher] student teachers and to investigate how these factors might influence their academic performance (dependent variable). Apart from the two factors above, the students' characteristics and entry skill qualifications were used as the independent variables in this study. There were two stages in this study. First, the development of culturally appropriates instrumentation and the pilot study to test the instruments for a final questionnaire. Second, the research used the ex-post factor design involving two strands of surveys: a student data survey using questionnaires, and interviews with students and educators. In the first strand, the study examined the students' characteristics, entry qualification skills, study approach preferences, levels of motivation, and the academic performance of 100 students entering the course with traditional and non-traditional modes of entrance. The second strand involved interviewing the selected students based on the results of data analysis and educators that teach the students to explore their perceptions of the variables above. Descriptive statistics, t-tests, correlation analysis, and regression analysis are used to analyse the data. The triangulation method was used to interpret the results of the interviewing analysis in support of the results of the data analysis. Generally, at the 0.05 significance level, the results show that there is a difference between the two groups of students (traditional and non-traditional) for all of the variables. The results of the exploratory correlation analysis at the 0.10 significance level, show that for traditional students, only mathematics has a strong relation with academic performance. However, through step-wise regression, it is identified that mathematics, Malay language, and surface approach were the possible influences on academic performance and this was represented by a diagrammatic picture. For non-traditional students, the results show that deep approach, surface approach, experienceltime away from study and intrinsic motivation have a significant correlation to academic performance. However, using stepwise regression, it is interesting to see that deep approach to study and experienceltime away from study were the better predictors of academic performance, and this is represented by a diagrammatic picture and a multiple regression plane. It was also interesting to discover that the independent variables for each group were significantly correlated. In conclusion, the results show that the two groups were different to each other in their study approaches, levels of motivation, characteristics, and entry skill qualifications and in the predictor that might be the influential factor on their academic performance, which was also supported by the interview findings. Some suggestions were proposed for the institutions, educators and the students themselves to help nurture the preparation for high quality, competent teachers. The outcomes of this study should lead to the enhancement of a teacher education programmes in higher education.